Activated carbon‐supported cobalt molybdate as a heterogeneous catalyst to activate peroxymonosulfate for removal of organic dyes. (1st October 2018) - Tao, Xiaoming; Wu, Yunhai; Wu, Yunying; Zhang, Bing; Sha, Haitao; Cha, Ligen; Liu, Ningning
Abstract : Activated carbon‐supported cobalt molybdate (CoMoO4 /AC) composite was conveniently fabricated using a simple hydrothermal route and high‐temperature calcination, aiming to create a novel heterogeneous catalyst for activation of peroxymonosulfate (PMS) to degrade organic dyes. The CoMoO4 /AC catalyst was characterized using scanning electron microscopy, powder X‐ray diffraction, energy‐dispersive spectroscopy, Fourier transform infrared spectroscopy, Raman spectroscopy, elemental mapping analysis and X‐ray photoelectron spectroscopy. Efficient catalytic activity, high stability and superior reusability were observed. Additionally, the catalytic performance of CoMoO4 /AC was systematically assessed through numerous controlled experiments and several operational factors, such as catalyst dosage, oxidant dosage, reaction temperature, initial pH and catalyst stability. Under the condition of CoMoO4 /AC = 0.1 g l −1, oxidant = 2.0 mM, dye = 100 mg l −1, T = 25°C, the removal of methylene blue reached 90% within 60 min without pH adjustment. Batch experiment results showed that the degradation of organic dye relied upon the dosage of catalyst and oxidant and reaction temperature. Further, high catalyst and oxidant dosage, as well as high reaction temperature, were favorable for dye removal. Moreover, quenching experiments suggested that the CoMoO4 /AC catalyst successfully activated PMS to generate sulfate and hydroxyl radicals. A rational mechanism is proposed based on a non‐radical process and a free radical process. The result revealed that the enhanced active sites were mainly ascribed to the synergistic effects between Co species and oxygen‐containing functional groups (especially ketone groups) on the catalyst surface. The findings of this study demonstrated the as‐prepared CoMoO4 /AC composite has potential superiority for refractory organic contaminant removal from water. Abstract : Activated carbon‐supported cobalt molybdate (CoMoO4 /AC) composite was fabricated conveniently, aiming to create a novel heterogeneous catalyst for activation of peroxymonosulfate to degrade organic dyes. A rational mechanism is proposed based on a non‐radical process and free radical process. The enhanced active sites were mainly ascribed to the synergistic effects between Co species and oxygen‐containing functional groups (especially ketone groups) on the catalyst surface.